Women’s Reproductive Health In A Tourism Setting: A Descriptive Study In Lovina, Bali - Luh Yenny Armayanti; Ni Komang Sulyastini; Putu Eva Yuni Dyantari; Luh Ari Arini; Putu Rama Pratama Karma; Putu Cynthia Devi Irmayanti (Jurnal Riset Kesehatan Nasional, 2026)
Women’s reproductive health is shaped by social, economic, cultural, and environmental factors, particularly in high-mobility settings such as tourism areas. In Lovina, Bali, tourism activities may influence reproductive health through lifestyle changes, psychosocial stress, and sexual behavior. This study aimed to describe the reproductive health profile of women living in this tourism area. A quantitative descriptive study with a cross-sectional design was conducted among 160 women aged 20–45 years, selected through purposive sampling. Data were collected using structured questionnaires and analyzed descriptively. Most respondents were aged 30–39 years, predominantly married, and had lived in the area for over five years. The majority experienced menarche at 13–14 years and reported normal menstrual cycles (21–35 days). Most had a history of pregnancy, commonly one to two pregnancies, although some had no live births. Contraceptive use was relatively high, especially injectable methods, but more than one-third had never used contraception. Miscarriage and unplanned pregnancy were reported by a notable proportion, while pregnancy complications were less common. Sexual behavior was generally low risk, though a small proportion reported sexually transmitted infections. Reproductive health was favorable, but gaps in contraception and STI prevention remain.  Keywords: Reproductive Health, Women, Tourism Area